“It's a good idea, but…”: a qualitative evaluation of the GoldiCare intervention in Norwegian home care services - Fischer, Heike; Lohne, Fredrik Klæboe; Fimland, Marius Steiro; Redzovic, Skender Elez (Frontiers in Health Services, 2025)
BackgroundAddressing high levels of physical strain among Norwegian home care workers is crucial if home care services are to continue to provide cost-effective and high-quality health care for people in their homes. Excessive physical demands may contribute to poor long-term musculoskeletal health and high sick leave rates among home care workers. Based on the Goldilocks Work Principle of redistributing an uneven distribution of physical demands to promote a working environment with a “just right” physical demands conducive to promoting long-term health, the GoldiCare intervention in home care services was conducted. The objective of this qualitative process evaluation study was to gain insights into how the implementation outcomes of acceptability, appropriateness, feasibility, adoption and fidelity, respectively, impacted the implementation of the GoldiCare intervention.MethodsWe conducted ten individual interviews with operations managers and five focus group interviews with home care workers from the intervention units. Interviews were transcribed verbatim and a three step-content analysis was employed to analyze interview material.ResultsOur analysis identified that although the intervention was considered broadly acceptable, there were several challenges corresponding to the dimensions of appropriateness, feasibility, adoption and fidelity. Major barriers were identified in particular with regard to appropriateness, that is underlying ways of measuring physical demands; and feasibility, that is barriers to implementing the tool. Further synthesis of these findings resulted in four core issues that need to be addressed if the GoldiCare intervention is to be successfully implemented in comparable Norwegian home care settings: proxy issues; complexity and unpredictability; organization-level issues; and operational autonomy.ConclusionThe findings provide valuable insights for future attempts to implement GoldiCare interventions in home care settings, highlighting the need to further integrate GoldiCare and other comparable types of intervention into the political, economic, sociocultural, professional, and technological context of home care services. Performed in the right way, such integration will also allow for more participatory input from those enacting such interventions. Trial registrationThis clinical trial was registered on 08/05/2022 under NCT05 487027.